2021
DOI: 10.1155/2021/6347404
|View full text |Cite
|
Sign up to set email alerts
|

Radiomic Features of 18F-FDG PET in Hodgkin Lymphoma Are Predictive of Outcomes

Abstract: Purpose. In the present study, we aimed to investigate whether the radiomic features of baseline 18F-FDG PET can predict the prognosis of Hodgkin lymphoma (HL). Methods. A total 65 HL patients (training cohort: n = 49; validation cohort: n = 16) were retrospectively enrolled in the present study. A total of 47 radiomic features were extracted from pretreatment PET images. The least absolute shrinkage and selection operator (LASSO) regression was used to select the most useful prognostic features in the trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…In line with our results, a high D max predicted a shorter PFS and OS in DLBCL patients ( 30 , 34 ). It has also been reported that a high D max is a poor prognostic factor of HL ( 36 ). Unlike TMTV or TLG, which are derived from lesion contours, D max is calculated as the distance between two lesions that were furthest apart.…”
Section: Discussionmentioning
confidence: 93%
“…In line with our results, a high D max predicted a shorter PFS and OS in DLBCL patients ( 30 , 34 ). It has also been reported that a high D max is a poor prognostic factor of HL ( 36 ). Unlike TMTV or TLG, which are derived from lesion contours, D max is calculated as the distance between two lesions that were furthest apart.…”
Section: Discussionmentioning
confidence: 93%
“…A total of 24 articles on lymphomas were included in this review [ 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 ], 13 of which studying diffuse large B-cell lymphoma (including 2 studies on gastro-intestinal lymphoma), 3 on follicular lymphoma, 3 on Hodgkin’s lymphoma, 2 on mantle cell lymphoma and 3 on other sub-types of lymphoma. 18F-FDG was the only tracer employed and all studies built radiomic models on baseline, pre-treatment PET images, often including clinical parameters and international prognostic indices.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies evaluated the role of PET radiomics and AI analysis in blood malignancies [ 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 ]. Lymphoma radiomics on 18F-FDG PET/CT was more often assessed on patients with DLBCL, in retrospective cohorts and for prognostic purposes.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Zhou and co-workers evaluated if the radiomic features of baseline FDG PET could predict the prognosis of Hodgkin lymphoma [39]. They found that Long-zone high gray-level emphasis and Dmax were independently correlated with 2-year progression-free survival.…”
Section: Discussionmentioning
confidence: 99%
“…Of those, 84% (n=72/88) achieved complete metabolic response (CMR) at end of therapy PET/CT de ned by Deauville score criteria below 4 [34][35][37][38][39][40]…”
mentioning
confidence: 99%